Insecticidal Activity of Cyperus rotundus L. and Datura stramonium L. Co-Administered with Sesame Oil Against African Bollworm Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) - Waleed, Elamin Elhaj; Abdelgadir, Ahmed Osman; Loai, Mohamed Elamin Elawad (Journal of Agronomy Research, 2021)
African bollwormis a worldwide-spread species that shows a high degree of polyphagia and it is considered as one of the main agricultural pests in the world. Laboratory experiments were conducted in the Research Laboratory, College of Agricultural Studies, Sudan University of Science and Technology to evaluate the lethal effect of C. rotundusand D. stramonium on the H. armigeraand to investigate the synergistic effect of sesame oil and tested extracts by dipping methods. Five concentrations (4%, 6%, 8%, 10% and 12%) were used for each plant extract in a Completely Randomized Design. Tubers ethanolic extract of C. rotundus at 12% concentration caused 90% mortality after 72 hrs of application, whereas 12% concentration of seeds ethanolic extract of D. stramonium generate only 70% mortality after 72 hrs of exposure. When sesame oil was added to each concentration of ethanolic extract of C. rotundus and D. stramonium it exhibited a synergistic effect. In fact, the 10% concentration scored 53.3% and 76.7% mortality, however, when mixed with sesame oil the mortality increased significantly to 83.3% and 100% for D. stramonium and C. rotundus respectively after 72 hrs of exposure. This  study clearly demonstrates that both tested plants have a lethal effect on the larvae of the African bollworm. However, tubers ethanolic extract of C. rotundus seems to be significantly more toxic than the seeds ethanolic extract of D. stramonium. This study also revealed that sesame oil has a synergistic effect when added to these plant extracts.
Keywords: Synergistic effect; Botanical extracts; Dipping method; Piperonyl butoxide.